Are financial benefits of financial globalization questionable until greater domestic financial development has taken place? - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
Purpose The issue of which financial initial conditions are necessary to materialize the benefits of financial globalization remains open to debate in the literature. In this paper, we try to put some empirical structure on the concept of financial threshold conditions in order to give policymakers guidance on the Kose et al.(2011) and Henry(2007) hypothesis. Its object is to assess if financial benefits of financial globalization are questionable until greater domestic financial development has taken place in developing countries. Design/methodology/approach In framing the financial dimension in a more concrete and tractable manner, we probe into the concerns of how domestic financial initial dynamics of depth(economic and financial systems), efficiency(banking and financial systems), activity (banking and financial systems) and size play-out in the financial development benefits of financial globalization. The estimation approach consists of assessing the impact of financial globalization through-out the conditional distributions of domestic financial development dynamics. Findings The introduction of previously missing financial dimensions into the debate generates a number of important findings. Only financial initial(threshold) conditions in depth and size are necessary to materialize the benefits of financial globalization. Domestic dynamics of efficiency and activity(credit) do not confirm the hypothesis. Practical implications Depending on the context of sampled countries, the appropriate role of policy has always been either to stem the tide of capital flows or encourage them. Policymakers who have been viewing their challenges exclusively from the later perspective for benefits in growth(finance) might be getting the financial dynamics badly wrong. Originality/value Blanket financial development policies may not reap the financial benefits of financial globalization until domestic financial dynamics of depth, efficiency, activity and size are critically considered. The introduction of the last three previously missing components in the literature sheds more light on the globalization-development nexus.
Keywords: F02; F21; F30; F40; O10; 330; Banking; International investment; Financial integration; Development